Simulation of acetone-water explosion in hydrothermal extraction reactor - Mohamed Yusoff, Hamdan; Lau, Kia Li; Izhar, Shamsul; Md Said, Mohamad Syazarudin (Elsevier, 2022)
This work investigates possible factors that lead to acetone-water explosion in a hydrothermal extraction reactor that happened in our laboratory. To begin with, acetone-water reactivity was checked in CAMEO. Next, pressure build-up curves at varying operating conditions were simulated in Aspen Batch Modeler. Analysis of variance (ANOVA) was conducted in IBM SPSS Statistical Software to determine the most significant factors causing the explosion. Results from CAMEO showed that the explosion was a boiling liquid expanding vapour explosion (BLEVE). Outputs from Aspen simulation indicated that the reactor pressure rise increased with the increment of acetone ratio, heating temperature and reactant total volume. The reactor wall ruptured as the pressure exceeded the maximum allowable working pressure. IBM SPSS showed that the heating temperature was the most significant factor causing the pressure to build-up within the reactor, followed by the acetone-water ratio and total reactant volume. Among all three factors, the heating temperature added to largest pressure build-up, especially when the temperature was increased near to 360 °C. The time required to trigger explosion was predicted to be within 13.8–15 min of heating.